2000
DOI: 10.1002/1096-9071(200101)63:1<8::aid-jmv1001>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of combined substitutions in nonstructural 5A region of hepatitis C virus and interferon response

Abstract: Interferon (IFN) therapy (+/- ribavirin) is the only currently available treatment for chronic hepatitis C virus (HCV), but is not effective for a majority of patients. Several studies have correlated IFN response with substitutions in a small region of the nonstructural 5A (NS5A) gene product of HCV, termed the interferon sensitivity determining region (ISDR). Many other studies, however, have been unable to verify this correlation. To address this issue, available data from published studies was used to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 44 publications
3
48
0
1
Order By: Relevance
“…This region has a particular importance since previous work by Enomoto et al [148] (1995) suggested that the genetic heterogeneity of the interferon sensitivity determining region domain of HCV NS5A (IFN sensitivity-determining region), linked to response to therapy in Japanese patients [148] . Although there seems not to be a consensus on this issue [85] , the published information supports the hypothesis that an association indeed exists between NS5A and response to therapy [149][150][151] . Some reports suggest that HCV NS5A protein can act in vivo repressing PKR function, and presumably allowing HCV to escape the antiviral effects of interferon [1,3,152,153] .…”
Section: Recombinationmentioning
confidence: 89%
“…This region has a particular importance since previous work by Enomoto et al [148] (1995) suggested that the genetic heterogeneity of the interferon sensitivity determining region domain of HCV NS5A (IFN sensitivity-determining region), linked to response to therapy in Japanese patients [148] . Although there seems not to be a consensus on this issue [85] , the published information supports the hypothesis that an association indeed exists between NS5A and response to therapy [149][150][151] . Some reports suggest that HCV NS5A protein can act in vivo repressing PKR function, and presumably allowing HCV to escape the antiviral effects of interferon [1,3,152,153] .…”
Section: Recombinationmentioning
confidence: 89%
“…15,16, In fact, after a statistical analysis of data from previously published studies, Witherell and Beineke 64 have recently proposed a redefinition of the classification of Enomoto et al, 16 in which only sequences with 1 to 2 aa changes are included in the intermediate type. The high frequency of aa changes within the ISDR in cirrhotic patients with HCC observed in this study would indicate that they may be infected by viral strains with increased sensitivity to interferon.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that sequence diversity and mutations within the NS3-encoding region associated with differential regulation of IRF-3 and low-level viral protein and NS3/NS4A abundance corresponded to an incomplete block of IRF-3 activation and function (10). Similarly, sequence diversity within the various encoding regions of the HCV RNA has been associated with sensitivity or resistance to IFN therapy in infected patients (16,25,48). This work collectively indicates that HCV genetic variation can influence the host response to infection and that HCV resistance to IFN is most likely supported through the actions of multiple viral proteins acting on specific cellular targets to attenuate host cell antiviral action.…”
mentioning
confidence: 99%